1999
DOI: 10.1128/aac.43.7.1788
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Activities of Tea Catechins against Helicobacter pylori

Abstract: The catechin epigallocatechin gallate showed the strongest activity of the six tea catechins tested against Helicobacter pylori(MIC for 50% of the strains tested, 8 μg/ml). It had bactericidal activity at pH 7 but not at pH ≤5.0. In infected Mongolian gerbils,H. pylori was eradicated in 10 to 36% of the catechin-treated animals, with significant decreases in mucosal hemorrhage and erosion. Tea catechins, therefore, may have therapeutic effects on H. pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
108
2
5

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(119 citation statements)
references
References 23 publications
2
108
2
5
Order By: Relevance
“…Schulz et al 56 suggested that the antimicrobial activity of polyphenols may result from their interaction with bacterial enzymes and proteins. Regarding the putative antimicrobial activity of green tea catechins, Sakanaka et al 57 and Mabe et al 58 reported an effective in vitro effect, while Amarowicz et al 59 showed that they had no antimicrobial effect on the bacterial population at 1 g kg −1 .…”
Section: Microbial Countsmentioning
confidence: 99%
“…Schulz et al 56 suggested that the antimicrobial activity of polyphenols may result from their interaction with bacterial enzymes and proteins. Regarding the putative antimicrobial activity of green tea catechins, Sakanaka et al 57 and Mabe et al 58 reported an effective in vitro effect, while Amarowicz et al 59 showed that they had no antimicrobial effect on the bacterial population at 1 g kg −1 .…”
Section: Microbial Countsmentioning
confidence: 99%
“…Tea catechins have therapeutic effects on H. pylori infection in vitro and in vivo. 26 Sulforaphane, a phytochemical, inhibits extracellular, intracellular, and antibiotic-resistant strains of H. pylori and prevents benzopyrene-induced gastric tumors. 27 Lactobacillus gasseri OLL2716 (LG21) is effective in both suppressing H. pylori and reducing gastric mucosal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…This activity seems to be proportional to the degree of polymerisation in polyphenol structure, to the nature of the linkage between units and to the presence of gallate substitution (Zhao et al 1999). Some tea components, including (-)-epigallocatechin gallate, (-)-epigallocatechin and (-)-epicatechin gallate, inhibited soybean lipoxygenase (Ho et al 1992) and catechin epigallocatechin gallate showed antibacterial properties against Helicobacter pylori (Mabe et al 1999). Cancer prevention using tea polyphenols has also been investigated in many studies (Okabe et al 1997;Fujiki et al 1999;Saeki et al 2000).…”
Section: Introductionmentioning
confidence: 97%